Perkembangan Pande Besi di Jodog 19301 - 1990an - , NDARU SIH WAHYONO; , Dr. Mutiah Amini S.S., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The focus of this research is about economics and social dynamics of pande besi in Jodog from 1930s to 1990s. This research is examined by using historical method which takes advantages from various sources such as primary sources, secondary sources and spoken sources. The sources were mostly taken from spoken historical method namely interview because the document was just a little since the earthquake some years ago. Primary sources are including photos, identity card, some training diplomas and appreciations in a limited number. On the other hand, secondary sources such as books and reports were also limited. The theme of the research was based on the existence of pande besi that was almost forgotten from the long history of agriculture and countryside. This research used the term pande besi because it was done in Javanese countryside. Pande besi in this place had been existed since some centuries ago. Pande besi in Jodog had passed some periods of time with its development. In 1930s, there were some many pande besi in Jodog such as pande gong, pande roda gerobak, and pande of agriculture appliances and home appliances. Pande besi kept holding on at that time though there was an economic crisis. In 1940s, pande besi became to decline because of some wars. However, in 1950s, pande besi got up and become a sector that cannot be separated from agriculture. 1970s was the anticlimax of the development of pande besi since the product of pande besi in Jodog had been spread out to the whole of Bantul area. In 1980s, the mechanization of pande besi began which is accompanied with the development of many big factories that became its rival in producing the products. The decline of pande besi happened which is indicated by the decrease of the number and willingness of the youth generations to make pande besi as their profession in 1990s.